Low copper-2 intake in Switzerland does not result in lower incidence of Alzheimer's disease and contradicts the Copper-2 Hypothesis. Issue 3 (February 2020) - Solioz, Marc
In recent years, the "Copper-2 Hypothesis" has been put forth in an attempt to explain the epidemic of Alzheimer's disease (AD) in the Western world. According to this hypothesis, "free" copper (copper-2) in drinking water, dietary supplements, and meat is the chief cause of the increased incidence of AD in recent decades. In contrast to the US, copper plumbing for drinking water is not used in Switzerland and tap water is very low in copper. Other "risk" factors including dietary supplements and meat consumption are also lower in Switzerland than in the US. Yet, the incidence of AD is closely similar in the two countries. This contradicts the Copper-2 Hypothesis. Impact statement: The Western world is faced with an Alzheimer's epidemic. Identifying the life style and anthropogenic factors involved has become a priority. This is a formidable challenge due to the complexity and the slow progression of the disease. A hypothesis put forth by George Brewer postulates divalent copper (copper-2), chiefly present in drinking water from copper pipes, to be a major risk factor for Alzheimer's disease. In Switzerland, copper pipes are not used for drinking water, but the frequency of Alzheimer's disease is similar to that of other Western countries. This contradicts Brewer's hypothesis and suggests that other factors are responsible for today's Alzheimer's epidemic.